Amperometric Measurements and Dynamic Models Reveal a Mechanism for How Zinc Alters Neurotransmitter Release. (20th January 2020) - Ren, Lin; Oleinick, Alexander; Svir, Irina; Amatore, Christian; Ewing, Andrew G.
Abstract: Zinc, a suspected potentiator of learning and memory, is shown to affect exocytotic release and storage in neurotransmitter‐containing vesicles. Structural and size analysis of the vesicular dense core and halo using transmission electron microscopy was combined with single‐cell amperometry to study the vesicle size changes induced after zinc treatment and to compare these changes to theoretical predictions based on the concept of partial release as opposed to full quantal release. This powerful combined analytical approach establishes the existence of an unsuspected strong link between vesicle structure and exocytotic dynamics, which can be used to explain the mechanism of regulation of synaptic plasticity by Zn 2+ through modulation of neurotransmitter release. Abstract : Die Struktur‐ und Größenanalyse des vesikulären dichten Kerns und dessen Halo durch TEM wurde mit der Messung und Modellierung der amperometrischen Einzelzellreaktionen kombiniert, um die Veränderungen der Vesikelgröße durch Zinkbehandlung zu untersuchen und den Mechanismus der Regulation der synaptischen Plastizität durch Zn 2+ durch Modulation der Neurotransmitterfreisetzung aufzuklären.